2001
DOI: 10.1177/103237320100600203
|View full text |Cite
|
Sign up to set email alerts
|

In praise of the “other” William Armstrong: a nineteenth century British engineer and early management consultant

Abstract: In praise of the "other" William Armstrong: a nineteenth century British engineer and early management consultant M Ma ar ri ia an nn ne e V V. . P Pi it tt ts s University of Warwick A Ab bs st tr ra ac ct t This paper is a tribute to an unsung accountant, economist and engineer, who had a clear understanding of modern concepts in accounting and finance, such as discounted cash flows, risk-adjusted discount rates and net present value (NPV), which are usually considered to be twentieth century developments. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The research literature on the 'old' industries of coal, iron and steel (e.g. Boyce, 1992,;Boyns and Edwards, 1995;Boyns and Edwards, 1997;Edwards et al, 1995;Pitts, 2001) and shipbuilding and engineering (e.g. McLean, 2006;McLean et al, 2015) provides evidence of the implication of costing in the production of strategic reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research literature on the 'old' industries of coal, iron and steel (e.g. Boyce, 1992,;Boyns and Edwards, 1995;Boyns and Edwards, 1997;Edwards et al, 1995;Pitts, 2001) and shipbuilding and engineering (e.g. McLean, 2006;McLean et al, 2015) provides evidence of the implication of costing in the production of strategic reports.…”
Section: Discussionmentioning
confidence: 99%
“…. (Boyns and Edwards, 1995;Brackenborough, McLean and Oldroyd, 2001;Pitts, 2001), continued to be relevant in the electrical supply industry of the Second Industrial Revolution. It may be noted that costing textbook author (Garke and Fells, 1887) Emile Garke was an electrical engineer who 'specialised in retrenchment and financial management' (Byatt, 1979, p. 189) and worked in both the Brush Electric Lighting Company (Section 3. above) and the Durham Electric Power Distribution Company (Section 6.2.2, above).…”
Section: Discussionmentioning
confidence: 99%
“…Parker (1968), Scorgie (1996) and Pitts (2001) have already demonstrated that DCF does not belong solely to the modern era, and the present study's focus on the 18th and 19th centuries can say little about the 1960s. Fortunately, there is more.…”
Section: Introductionmentioning
confidence: 93%
“…208-209;Fordyce, 1860, p. 53). Pitts (2001) has shown that the technique was already well established by the 1830s and gaining ground, thanks to the influence of the famous viewer, William Armstrong (1811-1896), but is it possible to pin-point its inception? Financial estimation was relatively sophisticated in the Tyneside coal industry from an early date.…”
Section: Introductionmentioning
confidence: 97%
“…There were two separate literatures, that of actuaries, engineers and land valuers, developing discount tables to value shares or assets according to mathematical formulae; and the economists and academic/practitioners who came to this approach via interest rates and opportunity cost of funds. In the UK, Armstrong, a mining engineer, used discounted cash flow to value mine leases and, indeed, mining companies for flotation (Pitts, 2001). Sutton (1882) prepared the first text book for the Institute of Actuaries, including a section on varying annuities.…”
Section: Accounting Business and Financial Historymentioning
confidence: 99%